ECONOMIC GROWTH AND WAYS TO MEASURE IT (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Economic growth is an increase in the volume of production of goods and creation of services in the country compared to previous years (periods). Ensuring economic growth is the main goal of any country's economic policy. Year after year, the increase in the number of the population and the continuous increase in the needs of people are among the main reasons that make economic growth a condition. Economic growth serves to raise the standard of living of the population and ensure the well-being of the people. The basis of economic growth is the development of the leading industries in the economy. This article provides information on Economic Growth and its measurement methods.